EKSISTENSI DEMOKRASI DAN KORUPSI BIROKRASI PELAYANAN PUBLIK DI INDONSIA - H. ISMAIL MZ (GANEC SWARA, 2021)
The purpose of this research is to study and analyze democracy is a system of government that is considered the best, not only because this system is the most historic discussion, but also the democratic system is considered the best system of governance in several countries in the world. Based on the opinions of experts and experts as well as the results of research on the choice of the democratic system in Indonesia, it is based on the desire for the existence of political parties as an extension of the people's hands as a channel for their aspirations. The existence of a political party is an absolute prerequisite for a country that practices a democratic system. Democracy and political parties are like two sides of a coin that cannot be separated from one another. That choosing a democratic system is assumed to be able to encourage efforts to eradicate corruption and reduce poverty. Through this research, the author tries to trace the relationship between the implementation of democracy and corruption of the public service bureaucracy in Indonesia. Democracy demands transparency and honesty, while corruption is anti-transparency and honesty.